Rural transformations and development - China in context the everyday lives of policies and people - Long, Norman; Jingzhong, Ye.; Yihuan, Wang.; Edward Elgar Publishing (Northampton, Mass. : Edward Elgar Pub., 2010)
This unique book explores the varied perspectives on contemporary processes of rural transformation and policy intervention in China. The expert contributors combine a critical review of current theoretical viewpoints and global debates with a series of case studies that document the specificities of China's pathways to change. Central issues focus on the dynamics of state-peasant encounters; the diversification of labour and livelihoods; out-migration and the blurring of rural and urban scenarios; the significance of issues of "value" and "capital" and their gender implications; land ownership and sustainable resource management; struggles between administrative cadres and local actors; and the dilemmas of "participatory" development.
pt. 1. Agrarian development and change in an era of globalization -- pt. 2. Encountering the state : peasant livelihood issues -- pt. 3. Urbanization of the countryside and migration dilemmas -- pt. 4. Politics of policy and participation.
Keywords: Rural development -- China; Electronic books